Indication of Horizontal DNA Gene Transfer by Extracellular Vesicles - Fischer, Stefanie; Cornils, Kerstin; Speiseder, Thomas; Badbaran, Anita; Reimer, Rudolph; Indenbirken, Daniela; Grundhoff, Adam; Brunswig-Spickenheier, Bärbel; Alawi, Malik; Lange, Claudia (PLOS ONE, 2016)
The biological relevance of extracellular vesicles (EV) in intercellular communication has been well established. Thus far, proteins and RNA were described as main cargo. Here, we show that EV released from human bone marrow derived mesenchymal stromal cells (BM-hMSC) also carry high-molecular DNA in addition. Extensive EV characterization revealed this DNA mainly associated with the outer EV membrane and to a smaller degree also inside the EV. Our EV purification protocol secured that DNA is not derived from apoptotic or necrotic cells. To analyze the relevance of EV-associated DNA we lentivirally transduced Arabidopsis thaliana-DNA (A.t.-DNA) as indicator into BM-hMSC and generated EV. Using quantitative polymerase chain reaction (qPCR) techniques we detected high copy numbers of A.t.-DNA in EV. In recipient hMSC incubated with tagged EV for two weeks we identified A.t.-DNA transferred to recipient cells. Investigation of recipient cell DNA using quantitative PCR and verification of PCR-products by sequencing suggested stable integration of A.t.-DNA. In conclusion, for the first time our proof-of-principle experiments point to horizontal DNA transfer into recipient cells via EV. Based on our results we assume that eukaryotic cells are able to exchange genetic information in form of DNA extending the known cargo of EV by genomic DNA. This mechanism might be of relevance in cancer but also during cell evolution and development.